Dampak Perselingkuhan Terhadap Perkembangan Psikologis Anak - Imtinan, Ghina; Ahmad, Mutia Aini (Batanang : Jurnal Psikologi, 2023)
Children's psychological development is development related to conditions that can affect children's daily lives both in the circle of friends and the surrounding community. There are so many factors that can affect the psychological development of children, including the family environment which will be the closest factor in the psychological development of children. Because basically the family is the first place for children to socialize after being born. The family is the first place for children regarding the social environment. If a child is in a harmonious and happy family, he will experience good psychological development, he will grow into a child who is physically, mentally and behaviorally healthy. However, it will be inversely proportional to children who grow and develop in an inharmonious family environment, such as the occurrence of an affair from one of their parents or both parents having an affair. These problems will have a tremendous impact, both on the perpetrators of the affair themselves, their partners and their children. Children will become victims of the infidelity committed by their parents. The impacts that will be obtained by the child include: there will be a child's distrust of a marriage relationship or distrust of the opposite sex, will cause anger and hatred in the child towards parents who have an affair, will cause indifference to their environment, children will close himself from the environment, the child will experience stress and the worst the child will experience depression. From the impact that the child gets, it will affect the development of the child in the future, both physically, psychologically and mentally. Efforts that can be made to maintain household harmony and maintain children's psychological development can be done by parents by building and maintaining small family harmony, by doing positive things together, spending weekends traveling together, being open to one another. So that the household is harmonious and the development and growth experienced by children is good and healthy physically, mentally and in behavior for the future.Keywords: Affair, Perkembangan Psikologis Anak, Children